INTRODUCTION OF THE LATIN SCRIPT IN THE UZBEK SSR: PROBLEMS AND CONTRADICTIONS (USING THE FERGANA REGION AS AN EXAMPLE) (Scientific journal of the Fergana State University, 2025)
This article examines the impact of the transition from the Arabic alphabet to Latin script in the Uzbek SSR during the 20s on the local culture and literacy system. It highlights that the Latinization process in the Fergana region was particularly challenging, with issues arising from shortages of textbooks, publishing personnel, and educational materials. In 1928, the Uzbek SSR government adopted a new writing system based on the Latin alphabet, which was promoted in the Fergana region through the newspaper “Yangi Farg‘ona” and other publications. The article emphasizes that this process led to a disconnect between the local population and their cultural heritage and historical written traditions. While the Soviet government portrayed this reform as “cultural progress”, the article argues that in practice, this process resulted in the weakening of national culture and a decline in literacy levels.